Islamic law and endowment - Khan, Muhammad Moinuddin (Discovery Pub. House, 2011)
Present modest work, Islamic Law and Endowment is but the result of painstaking efforts of the undersigned, who meticulously worked in giving this final shape of a a book on Islamic law.